The Rohingya: ethnic nationalism, domestic diversionary targets, and Burmese post-colonial nation building - Abd-El-Barr, Ibrahim (AUC Knowledge Fountain, 2019)
This dissertation explores the question of whether recurring episodes of violence, forced displacement, and other forms of repression against the ethno-religious sub-nationalist identity group, the Rohingya, across Burma's (Myanmar) modern history, are rooted in the implications of post-colonial nation-building or represent independent and self-contained incidents of communal/ethnic violence. The sub-question of whether the modern construct of the Burmese state accurately fits the description of a modern nation-state or whether other paradigms or ideal types better capture the development of the post-colonial Burmese state, is also explored. By revisiting the main events/national framework which have amounted to the Rohingya's exclusion from Burmese nation-building as well as tracing a historical trajectory of the episodes of violence/forced displacement of the Rohingya against the backdrop of the surrounding political and economic contexts, it is argued that the Rohingya have been targeted as domestic diversionary targets for the Burmese military regime's constant failures in managing the state's economic and financial sectors, defeats in electoral politics, and compromises to its presumed sources of legitimacy and public acceptance. Utilizing the instrumentalist diversionary theory of war, or the scapegoat hypothesis, it is demonstrated that violence against the Rohingya not only falls under a systematic and recurring process of exclusion from post-colonial nation-building but also the development of the Burmese state to resemble a garrison state has facilitated the targeting of the Rohingya as a domestic/territorial diversionary target or option.